TIME HEADWAY ANALYSIS TO DETERMINE THE ROAD CAPACITY - I Wayan Suweda (JURNAL SPEKTRAN, 2016)
ABSTRACT: In developed countries, road capacity values derived from time headway is in accordance to their local traffic characteristics. In theory, time headway standards are developed using statistics models. These standards however, are not necessarily relevant to use in Indonesia. This is because of the differences in traffic conditions and motorists behaviours between those in developed countries and Indonesia. This study is to develop the time headway distribution model and subsequently to determine lionk-road capacity in the city of Denpasar, Bali Province. The study consists of time headway data analysis, model calibration and validation and road capacity values??determination. The study found that normal distribution model fitted the local traffic conditions. Road capacity values are of  2,466 pcus/hour and 2,900 pcus/hour obtained from time headway model and the Indonesian Road Capacity Manual (MKJI) respectively.